Effects of Plant Extracts on Dentin Bonding Strength: A Systematic Review and Meta-Analysis - Zhao, Shikai; Hua, Fang; Yan, Jiarong; Yang, Hongye; Huang, Cui (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: To systematically review in vitro studies that evaluated the effects of plant extracts on dentin bonding strength. Materials and Methods: Six electronic databases (PubMed, Embase, VIP, CNKI, Wanfang and The Cochrane Library) were searched from inception to September 2021 in accordance with the Preferred Reporting Items for Systematic Reviews (PRISMA). In vitro studies that compared the performance of dental adhesives with and without the plant extracts participation were included. The reference lists of the included studies were manually searched. Two researchers carried out study screening, data extraction and risk of bias assessment, independently and in duplicate. Meta-analysis was conducted using Review Manager 5.3. Results: A total of 62 studies were selected for full-text analysis. 25 articles used the plant extracts as primers, while 5 added the plant extracts into adhesives. The meta-analysis including 14 articles of in vitro studies investigated the effects of different plant extract primers on dentin bonding strength of etch-and-rinse and self-etch adhesives, respectively. The global analysis showed statistically significant difference between dental adhesives with and without plant extract primers. It showed that the immediate bond strength of dental adhesives was improved with the application of plant extract primers. Conclusion: The application of proanthocyanidin (PA) primers have positive effect on the in vitro immediate bonding strength of dental adhesives irrespective of etch-and-rinse or self-etch modes.